Use of HIV counseling and testing and family planning services among postpartum women in Kenya: a multicentre, non-randomised trial. Issue 1 (December 2015) - Kimani, James; Warren, Charlotte; Abuya, Timothy; Ndwiga, Charity; Mayhew, Susannah; Vassall, Anna; Mutemwa, Richard; Askew, Ian
Abstract Background Addressing the postnatal needs of new mothers is a neglected area of care throughout sub-Saharan Africa. The study compares the effectiveness of integrating HIV and family planning (FP) services into postnatal care (PNC) with stand-alone services on postpartum women's use of HIV counseling and testing and FP services in public health facilities in Kenya. Methods Data were derived from samples of women who had been assigned to intervention or comparison groups, had given birth within the previous 0–10 weeks and were receiving postnatal care, at baseline and 15 months later. Descriptive statistics describe the characteristics of the sample and multivariate logistic regression models assess the effect of the integrated model of care on use of provider-initiated testing and counseling (PITC) and FP services. Results At the 15-month follow-up interviews, more women in the intervention than comparison sites used implants (15 % vs. 3 %;p  < 0.001), while injectables were the most used short-term method by women in both sites. Women who wanted to wait until later to have children (OR = 1.3;p  < 0.01; 95 % CI: 1.1–1.5), women with secondary education (OR = 1.2;p  < 0.05; 95 % CI: 1.0–1.4), women aged 25–34 years (OR = 1.2;p  < 0.01; 95 % CI: 1.1–1.4) and women from poor households (OR = 1.6;p  < 0.001; 95 % CI: 1.4–1.9) were associated with FP use. Nearly half (47 %) and about one-third (30 %) of mothers in the intervention and comparison sites, respectively, were offered PITC. Significant predictors of uptake of PITC were seeking care in a health center/dispensary relative to a hospital, having a partner who has tested for HIV and being poor. Conclusions An integrated delivery approach of postnatal services is beneficial in increasing the uptake of PITC and long-acting FP services among postpartum women. Also, interventions aimed at increasing male partners HIV testing have a positive effect on the uptake of PITC and should be encouraged. Trial registration ClinicalTrials.govNCT01694862